A new species of lutrine opossum, genus Lutreolina Thomas (Didelphidae), from the South American Yungas - Martínez Lanfranco, Juan A. (2014)
This study presents the most comprehensive systematic revision of the genus Lutreolina to date, by means of genetic (mitochondrial DNA of 22 specimens) and morphologic (assessment of 262 specimens) evidence. Molecular analyses were based on cytochrome-b gene sequences from 22 individuals collected at 18 localities from Argentina, Bolivia, Brazil, Paraguay, and Uruguay, which are currently allocated to L. crassicaudata. Results indicate that Lutreolina has sharp phylogeographic structure, with 2 reciprocally monophyletic groups (2.7% divergent, whereas intraclade variation is minimal) occurring east and west of the Dry Chaco, where Lutreolina is absent. The eastern clade includes populations from eastern Paraguay, northeastern central Argentina, southern Brazil, and Uruguay. These populations were traditionally allocated to the subspecies L. c. crassicaudata and L. c. paranalis, whose monophyly is not supported in our study. Therefore, eastern populations are all assigned here to the nominotypic subspecies. The western clade is restricted to montane Yungas forests of northwestern Argentina and southern Bolivia, a very different environment from those inhabited by Lutreolina elsewhere (i.e., lowland savannah grasslands). The populations from the Yungas also are morphologically distinct, in size, shape, and in discrete characters of the skull and dentition. We found that these populations belong to a different species than that of the eastern lowlands. Because no taxonomic name is available to apply to these populations, we name and describe a new species of lutrine opossum to encompass them.